Effect of Competence, Work Environment, Work Discipline and Work Achievement on Employee Performance - Nurhaeda Z, Nurhaeda; Bahasoan, Shandra; Devita, Devita (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to examine the influence of competency, work environment, work discipline and work achievement on employee performance. In this research, the research methods used are descriptive and verification research. The population in this study were all employees of PT Bosowa Propertindo Makassar, totaling 35 employees. The sampling technique in this research is a saturated sample. The sample in this research was all employees of PT Bosowa Propertindo Makassar, namely 35 people. The analytical method used in this research is multiple linear regression analysis. The results of this research found that competence, work environment, work discipline and work achievement, both simultaneously and partially, have a positive and significant effect on employee performance.